Issues of International Students’ Academic Adaptation in the ESL Writing Class: A Mixed-Methods Study - Park, Eunjeong (Journal of International Students, 2016)
Despite the contribution to economic and social impact on the institutions in the United States, international students’ academic adaptation has been always challenging. The study investigated international graduate students’ academic adaptation scales via a survey questionnaire and explored how international students are academically adapted in the U.S. college setting through qualitative research with class observations, field notes, and semistructured interviews. In addition, the use of lexical bundles was examined as one of the academic literacy adaptation indicators. The quantitative and qualitative results revealed international graduate students’ academic adaptation in different angles. The implications of the findings are discussed.